Calidad bacteriológica del agua para consumo en tres regiones del Perú - Tarqui-Mamani, Carolina (2016)
ABSTRACT Objective To estimate the bacteriological quality of drinking water in Huancavelica, Cajamarca and Huánuco during 2012-2013 Material and Methods A cross-sectional study was conducted. Sampling was probabilistic, stratified and multistage. The sample included 706 households. The Readycult ® kit was used to assess the presence of total coliforms and E. coli. 100 mL of water used for food preparation was collected. The determination of residual chlorine was performed by semiquantitative analysis using Chlorine Test Reagent ®. It was established as the ideal residual chlorine concentration ≥0,5 mg/L. The statistical analysis considered the necessary weight for complex samples. We calculed percentages and chi square. The informed consent of the head of household is requested. It was defined as good bacteriological quality of water: water sample with adequate free chlorine, in the absence of total coliforms and E. coli. Results The samples tested, 78.6 % had total coliforms in Cajamarca, Huancavelica and 65.5 % at 64.1 % in Huanuco. The 72.0 % had E. coli in Cajamarca, Huancavelica 37.4 % and 17.5 % in Huánuco. In Cajamarca, 8.6 % of the water samples were of good bacteriological quality, while in Huancavelica was 4.3 % and Huanuco, 7.2 %. Conclusions Most of the water samples were of poor bacteriological quality. Most of the water samples had total coliforms. Three-quarters of households in Cajamarca, Huancavelica third and almost one fifth of Huanuco had the presence of E. coli in drinking water.